Chromium isotope cycling in the water column and sediments of the Peruvian continental margin. (15th July 2019) - Bruggmann, S.; Scholz, F.; Klaebe, R.M.; Canfield, D.E.; Frei, R.
Abstract: Chromium (Cr) isotope fractionation is sensitive to redox changes and the Cr isotopic composition (δ 53 Cr) of sedimentary rocks has been used to reconstruct marine redox conditions and atmospheric oxygenation in the past. However, little is known about the behaviour of chromium isotopes across modern marine redox boundaries. We investigated Cr concentrations and δ 53 Cr variations in seawater and sediment across the Peruvian oxygen minimum zone (OMZ) to provide a better understanding of Cr cycling in the ocean. We found that seawater δ 53 Cr values ranged from 0.02 ± 0.16‰ to 0.59 ± 0.11‰ (2SD) and sediment values from 0.31 ± 0.07 to 0.92 ± 0.12‰. Neither Cr concentrations nor δ 53 Cr values in the water column revealed significant shifts across the oxic-anoxic boundaries. Instead, processes that operate at a local scale, such as Cr scavenging by Fe-rich particles and Cr release from reducing sediments, are identified as the main controls on Cr concentrations and isotope compositions in the water column. The δ 53 Cr values of sediments deposited in permanently anoxic waters (0.77 ± 0.19‰, n = 5) are significantly different from the δ 53 Cr values of sediments deposited in oxic bottom waters (0.46 ± 0.19‰, n = 4). This suggests that sediment Cr concentrations and δ 53 Cr values are to some extent influenced by water column redox (e.g. reductive dissolution and transport of Fe oxides) and/or early diagenetic (e.g. redistribution of Cr during phosphogenesis) processes as well as biologic activity. Our data demonstrate that local scale water column redox gradients and sediment exchange can lead to a large range of δ 53 Cr values in sediments, comparable to the range found in the entire geologic record to date. Given the increasing prominence of Cr isotope measurements in constraining atmospheric oxygenation in deep time, we argue that the processes influencing Cr cycling under different conditions and from the water column to the sediment need to be better resolved to verify the utility of such measurements as paleoenvironmental proxies.